2015
DOI: 10.1590/1806-9282.61.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Delinquency and association with behavioral disorders and substance abuse

Abstract: Conflict of interest: noneObjective: to determine the incidence and associations of attention deficit-hyperactivity disorder (ADHD), conduct disorder (CD), and substance abuse disorder (SAD) in adolescents in conflict with the law in a Brazilian cohort. Methods: the Brazilian version of the Schedule for Affective Disorders and Schizophrenia for School Aged-Children (K-SADS-PL) was administered to 69 adolescent boys who were incarcerated for 45 days in the city of Curitiba, Brazil. Results: mean age was 15.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 35 publications
0
17
0
22
Order By: Relevance
“…21,[32][33][34]58,62 The diagnostic interviews were mostly conducted by psychiatrists, 33,34,41,45,[47][48][49]54,55,58,60,62,65,67 clinical psychologists, 21,43,56,72 researchers and research assistants, 27,36,46,70 or teams with diverse backgrounds. 19,28,32,35,37,38,40,50,51,59,64 Most studies reported the types of offenses, and in accordance with previous research, 74 we calculated the proportion of adolescents who committed violent offenses, which ranged from 6.0% 60 to 86.0%. 58 Figure 2 presents gender-specific prevalence estimates.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…21,[32][33][34]58,62 The diagnostic interviews were mostly conducted by psychiatrists, 33,34,41,45,[47][48][49]54,55,58,60,62,65,67 clinical psychologists, 21,43,56,72 researchers and research assistants, 27,36,46,70 or teams with diverse backgrounds. 19,28,32,35,37,38,40,50,51,59,64 Most studies reported the types of offenses, and in accordance with previous research, 74 we calculated the proportion of adolescents who committed violent offenses, which ranged from 6.0% 60 to 86.0%. 58 Figure 2 presents gender-specific prevalence estimates.…”
Section: Resultsmentioning
confidence: 69%
“…12,19,21,27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] We combined them with the 25 surveys identified in the previous review. 28, Two studies 12,69 were based on the same sample, which provided 12,28,40,42,[50][51][52][53]57,[59][60][61]63,66,68,69,72,73 ; six were from the United Kingdom (n ¼ 1,145) 27,44,54,55,62,64 ; three were from Canada (n ¼ 408) 37,<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,4648 These disorders are known to be risk factors for delinquency, interactions with the juvenile justice systems, and homelessness. 49 For example, in France 25% of homeless people and 20% of adults in jail were formerly youths in the CWS. 50,51 …”
Section: Discussionmentioning
confidence: 99%
“…These disorders are known to be risk factors for delinquency, interactions with the juvenile justice systems, homelessness and suicide [18]. Also, childhood and adolescent mental disorders significantly impairs the overall functioning and quality of life of affected individuals [19][20][21], as well as posing substantial economic burden on both the family and the nation [22].…”
Section: Introductionmentioning
confidence: 99%